1993
DOI: 10.1002/1097-0142(19931101)72:9<2638::aid-cncr2820720919>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Linear regressive analysis using prostate-specific antigen doubling time for predicting tumor biology and clinical outcome in prostate cancer

Abstract: Background. This study was undertaken to calculate the prostate‐specific antigen doubling time (PSA‐DT) of prostate cancers recurrent after external beam radiation therapy and to investigate if a correlation exists between the PSA‐DT and the clinical behavior of prostate cancer as a possible reflection of the tumor doubling time. Methods. Twenty‐two patients treated with external beam radiation between October 1985 and October 1990 for clinical stages B1, B2, and C (T2a, T2b, T3) prostate cancer experienced PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…Several studies have suggested that it is between several months and 4 years. 27,28 If the tumor volume doubling time were three years, patients 60 years or younger with tumor volumes of 0.5 ml might be likely to develop clinically significant prostate cancer based on the average life expectancy. If tumors have higher Gleason scores, the potential for metastasis may increase and these patients may present with clinically significant prostate cancer sooner.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that it is between several months and 4 years. 27,28 If the tumor volume doubling time were three years, patients 60 years or younger with tumor volumes of 0.5 ml might be likely to develop clinically significant prostate cancer based on the average life expectancy. If tumors have higher Gleason scores, the potential for metastasis may increase and these patients may present with clinically significant prostate cancer sooner.…”
Section: Discussionmentioning
confidence: 99%
“…D'Amico and Hanks, evaluating the same 22 patients who demonstrated PSA failure after receiving RT at FCCC, described a linear correlation between the PSADT and the clinical disease free interval after PSA failure. 15 Using linear regression analysis techniques, it was noted that clinical failure should manifest on average 4.5 times the PSADT. Lee et al subsequently described the natural history of a large group of patients with an increasing PSA profile after receiving definitive RT at FCCC.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5 D'Amico and Hanks found that, following radiation therapy for prostate cancer, PSA doubling time was linearly correlated with the interval to clinical relapse after PSA failure. 5 They recommended observation rather than treatment for patients with PSA doubling times of ! 18 months, because the disease may not become clinically apparent during the patient's life time.…”
Section: Discussionmentioning
confidence: 99%